Key drivers of consumer acceptance of technology use in food production: synergy between health benefits and psychological factors - Lee, Ahmed Thaufiq; Ariffin, Hashim Fadzil; Mohd Akhir, Irina; Devi, Mazarina (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
Growing numbers of people were forced to dedicate a substantial amount of time every day to gathering and hunting in order to meet their own families' food needs due to limitations in food processing and storage methods. This research investigated the influence of perceived health benefits and psychological factors on consumers’ acceptance of technology applied in food production. The health benefits include direct health benefits, reduction of disease risk, and better life conditions. The psychological factors attribute consists of information obtained, evaluation of new technology, and understanding of hazards. The closed-ended questionnaires were applied to collect data from an estimated sample size of 128 respondents in Penang State, Malaysia. The results indicated that most of the respondents were male, between the ages of 18 and 30. The research discovered that the influence of perceived health benefits and psychological factors had a significant influence on consumers’ acceptance of technology applied in food production. The research results also revealed that most respondents agreed that lack of knowledge is a major factor in why people refuse to accept the technological influence on food production. This study concludes that manufacturers, government agencies, and advocacy groups must collaborate and cooperate to increase public awareness about genetically modified foods.